A unique family of Mrr-like modification-dependent restriction endonucleases - Zheng, Yu (Oxford University Press, 2010)
Mrr superfamily of homologous genes in microbial genomes restricts modified DNA in vivo. However, their biochemical properties in vitro have remained obscure. Here, we report the experimental characterization of MspJI, a remote homolog of Escherichia coli’s Mrr and show it is a DNA modification-dependent restriction endonuclease. Our results suggest MspJI recognizes (m)CNNR (R = G/A) sites and cleaves DNA at fixed distances (N(12)/N(16)) away from the modified cytosine at the 3′ side (or N(9)/N(13) from R). Besides 5-methylcytosine, MspJI also recognizes 5-hydroxymethylcytosine but is blocked by 5-glucosylhydroxymethylcytosine. Several other close homologs of MspJI show similar modification-dependent endonuclease activity and display substrate preferences different from MspJI. A unique feature of these modification-dependent enzymes is that they are able to extract small DNA fragments containing modified sites on genomic DNA, for example ∼32 bp around symmetrically methylated CG sites and ∼31 bp around methylated CNG sites. The digested fragments can be directly selected for high-throughput sequencing to map the location of the modification on the genomic DNA. The MspJI enzyme family, with their different recognition specificities and cleavage properties, provides a basis on which many future methods can build to decode the epigenomes of different organisms.